Sulfide based anode for lithium ion battery - Teoh, Luen Ming. (2011)
High-capacity anode is needed for lithium ion battery to meet future energy demand of portable electronics. The electrochemical measurements between Ge, GeS and GeS2 as anode were carried out. Two electrode fabrication methods i.e. conventional mixing and CVD method were presented. GeS and GeS2 showed better cycling performance than Ge. Both of them exhibited higher discharge capacity, which were 393 mAh/g and 349 mAh/g for GeS and GeS2 respectively after 50 cycles. The improved cycling performance is believed to be due to the formation of Li2S phase which acts as buffering matrix during charge and discharge reaction. GeS2 electrode fabricated by CVD method also showed better cycling performance due to strong adhesion of thin film to the electrode as compared to electrode fabricated by conventional mixing method. Ge electrode fabricated at lower temperature region in CVD furnace also displayed better cycling performance due to the deposition of smaller particles on the electrode.